PERSEPSI MAHASISWA PLS ANGKATAN 2014 TERHADAP PROGRAM STUDI PENDIDIKAN LUAR SEKOLAH DI FKIP UNIVERSITAS RIAU PEKANBARU - Bahar, Aswandi Bahar Aswandi; ', Sultini Sultini; ', Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine students' perceptions of PLS the year of 2014 to study the program of non-formal Education Riau University, Pekanbaru. The Formulation of the problem is that what is the student PLS perception the year of 2014 to the study program of non-formal education at FKIP Riau University Pekanbaru?. The type of the study is a descriptive by using quantitative approach which aims to describe the results of research by the numbers. The sampling technique was using random sampling techniques. Data collection techniques in this study was the questionnaire technique, totaling 66 items. The questionaire was tried out to 20 students of non respondent. The result was that 12 of 66 items was not valid. The sample of the research was 36 student of non-formal education study program. The result showed that students' perceptions to the study program of sub-indicator of means was good (77,36%). Compared to sub-lecturer (76,71%). This means that the students perception to the study program of non-formal education dealing with serving to all student activities is good.Keywords: Perception of Students, Program of non-formal Education